2005
DOI: 10.2174/1568010054526331
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Mechanisms of Glucocorticoids Targeting Granulocytes

Abstract: Asthmatic inflammation involves the recruitment and activation of inflammatory cells, and changes in the structural cells of the lung and asthma are characterized by an increased expression of components of the inflammatory cascade including cytokines, chemokines, growth factors, enzymes, receptors and adhesion molecules. The increased expression of these proteins seen in asthma is generally the result of enhanced gene transcription, since many of the genes are not expressed in normal cells but are induced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 114 publications
(174 reference statements)
1
17
0
Order By: Relevance
“…Clinical and review studies demonstrated that the treatment of asthma with corticosteroids inhibits the infiltration of eosinophils and lymphocytes in the bronchial mucosa and diminishes Th2 cytokine expression [24,25]. Dexamethasone blocked eosinophil recruitment into lung, and Th2 cytokine and IgE expression (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical and review studies demonstrated that the treatment of asthma with corticosteroids inhibits the infiltration of eosinophils and lymphocytes in the bronchial mucosa and diminishes Th2 cytokine expression [24,25]. Dexamethasone blocked eosinophil recruitment into lung, and Th2 cytokine and IgE expression (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…Ketotifen, an antiallergy drug having H1-receptor antagonist activity, is widely used for allergic disease and known to be effective in reducing sneezing (Grant et al, 1990). Glucocorticoid is also widely used in the treatment of inflammatory disease, including allergic inflammation (Caramori and Adcock, 2005). Thus we evaluated the effects of ketotifen and dexamethasone on our model of allergic rhinitis in B10.S mice.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with AP-1 or NF-kB decoy ODN significantly decreased IL-1b, TNF-a, and MPO activities in the tissue contents, which coincided well with the results of our histological examinations (Figure 6a-c). [33][34][35][36][37][38][39][40] Although AP-1 is a major immunoregulatory as well as proinflammatory transcription factor, 21,[27][28][29][30][45][46][47] nothing is known to have been reported regarding the effect of AP-1 inhibition by a decoy ODN on intestinal inflammation. In the present study, we designed a ds decoy ODN binding to AP-1-specific nucleotide sequences and investigated its efficacy to prevent murine experimental DSS-induced colitis.…”
Section: Effects Of Decoy Odns On Expression Of Proinflammatory Cytokmentioning
confidence: 99%